Analysis of the Effect of Infrastructure Development on Land Prices in Cinere and Beji Districts, Depok City - Cindar Hari Prabowo; Joko Adianto (Konfrontasi: Jurnal Kultural, Ekonomi dan Perubahan Sosial, 2022)
The surge in housing prices in cities has triggered the emergence of many problems related to urban settlements, starting from the construction of housing that is far from the city center, congestion problems, pollution, to encouraging the occurrence of many informal slum settlements. This causes a shift in settlements to supporting areas, especially Jabodetabek. Residential prices are dominantly influenced by high land prices. Infrastructure development has a major influence on economic growth and the development of an urban area. However, this is not easy to apply in the Depok City area, especially in the Cinere and Beji District areas. Housing development is very rapid but must be followed by the development of facilities and infrastructure. The purpose of this study was to analyze the influence of infrastructure development factors such as road network (accessibility), availability of facilities (transportation network, electricity network, telephone network, clean water network, educational facilities, health facilities) and residential neighborhoods based on the opinions of housing residents on land prices in residential neighborhoods in Depok City, especially in Cinere Dan Beji Districts. The research method used is research using a mixture of quantitative and qualitative methods in stages considering the complexity of the problem. Quantitative methods will be used to look at housing-related data as a basis, then to NJOP analysis as a basis for land prices. The results of this study indicate that in general, the data analysis shows compatibility with the literature that has been done, that land prices are very significantly influenced by the accessibility of the main highway network and the presence of commercial equipment to fulfill needs.